"Lost in translation: Seeing the forest by focusing on the trees". Issue 2 (1st February 2018) - Hughes, Kelly T.; Chevance, Fabienne F. V.
ABSTRACT: A complex process translates messenger RNA (mRNA) base sequence into protein amino acid sequence. Transfer RNAs must recognize 3-base codons in the mRNA to insert the correct amino acids into the growing protein. Codon degeneracy makes decoding complicated in that multiple (synonymous) triplets can encode a single amino acid and multiple tRNAs can have the same anticodon. Over the last twenty years, new developments in structural biology, genome sequencing and bioinformatics has elucidated the intricacies of the ribosome structure and the details of the translation process. High throughput analyses of sequence information support the idea that mRNA folding has a major effect on expression for codons at the 5′-end of mRNA (N-terminal region of a polypeptide). Despite a forest of sequence data, significant details of the complex translation process can escape detection. However, a sensitive translation assay has allowed a single tree in this forest to be revealing.